The Effects of Stand Density on the Growth of Winter Rapeseed in an Agroforestry Intercropping System in the Red Soil Slopes of Southern China - Xin Luo; Xianghui Lu; Haina Zhang; Haolong Wan; Yue Zhang; Xiaoying Feng (Plants)
Agroforestry systems can improve land use efficiency and increase the output of agricultural and forestry products. In this study, a camphor forest–winter rapeseed composite system was used as the research object from 2023 to 2024. A randomized block experiment was used to set different slopes, S1, S2, and S3 (5°, 10°, and 15°), and camphor forest densities D1, D2, and D3 (row spacing of 1.5 m × 1.5 m, 1.0 m × 1.5 m, 1.0 m × 1.0 m) to compare a single crop (CK) of winter rapeseed and analyze its growth status. This study showed that slope and camphor forest density significantly affected the growth indicators of winter rapeseed. Among the intercropping treatments, S1D2 (5°, 1.0 m × 1.5 m) performed best. In the late growth period of winter rapeseed (flowering to maturity), the treatment increased leaf area index, relative chlorophyll content, root system indicators (length, surface area, volume), theoretical yield, and actual yield, and it increased the aboveground biomass per unit area. Although the actual yield of intercropping on slopes S1, S2, and S3 was 2.52%, 2.82%, and 1.72% lower than that of monocropping, respectively, the ground surface was exposed and idle in winter after the camphor trees were cut down in September. Intercropping winter rapeseed with camphor trees can improve land utilization and increase surface coverage. The results showed that the S1D2 (5°, 1.0 m × 1.5 m), S2D1 (10°, 1.5 m × 1.5 m), and S3D1 (15°, 1.5 m × 1.5 m) treatments performed well in terms of biomass accumulation and yield, and they can be used as recommended intercropping patterns for different slopes.